The influence of hyperthermia on intracranial pressure, cerebral oximetry and cerebral metabolism in traumatic brain injury. (3rd July 2017) - Nyholm, Lena; Howells, Tim; Lewén, Anders; Hillered, Lars; Enblad, Per
Abstract: Background: Hyperthermia is a common secondary insult in traumatic brain injury (TBI). The aim was to evaluate the relationship between hyperthermia and intracranial pressure (ICP), and if intracranial compliance and cerebral blood flow (CBF) pressure autoregulation affected that relationship. The relationships between hyperthermia and cerebral oximetry (Bti pO2 ) and cerebral metabolism were also studied. Methods: A computerized multimodality monitoring system was used for data collection at the neurointensive care unit. Demographic and monitoring data (temperature, ICP, blood pressure, microdialysis, Bti pO2 ) were analyzed from 87 consecutive TBI patients. ICP amplitude was used as measure of compliance, and CBF pressure autoregulation status was calculated using collected blood pressure and ICP values. Mixed models and comparison between groups were used. Results: The influence of hyperthermia on intracranial dynamics (ICP, brain energy metabolism, and Bti pO2 ) was small, but individual differences were seen. Linear mixed models showed that hyperthermia raises ICP slightly more when temperature increases in the groups with low compliance and impaired CBF pressure autoregulation. There was also a tendency (not statistically significant) for increased Bti pO2, and for increased pyruvate and lactate, with higher temperature, while the lactate/pyruvate ratio and glucose were stable. Conclusions: The major finding was that the effects of hyperthermia on intracranial dynamics (ICP, brain energy metabolism, and Bti pO2 ) were not extensive in general, but there were exceptional cases. Hyperthermia treatment has many side effects, so it is desirable to identify cases in which hyperthermia is dangerous. Information from multimodality monitoring may be used to guide treatment in individual patients.